KARAKTERISTIKA ALIRAN PRIMER DAN SEKUNDER PADA BELOKAN SALURAN: (Studi komparatif data eksperimental, lapangan dan persamaan empiris - YANUAR A, ARRIZKA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The issues of migration, erosion, and sedimentation in open channel became attractive hydrodynamic phenomenon to be investigated. Natural channel such as rivers with plural bends are difficult to mathematically illustrate flow characteristics because of the occurrence of discharge fluctuation and bed form. Experimental investigation was conducted to determine flow characteristics precisely by smaller scale. This investigation compared velocity profile as the result of laboratory study and field study to velocity profile obtained from empirical equations in order to determine velocity profile difference. Based on the investigation done by Sumiyadi et al (2014), the experimental data had two conditions, erodible bed and fixed bed with ks = 1 mm and ks = 1.18 mm respectively, degree of curvature 180o, width 0.5 m, height 0.4 m, radius of curvature in centerline 1.25 m measured by ADV made in SONTEK. Field study was conducted by Muharis et al (2014) at Mataram Irrigation Channel with width 4.18 m, degree of curvature 57o, radius of curvature in centerline 50 m measured by calibrated Current Meter made in UGM. Longitudinal velocity profiles (us) in sharp open channel bend have two characteristics, there are velocity profiles are flatter than logarithmic profile of the velocity in the near water surface and the maximum velocity occurs near the bed (0.35h). The smallest difference between longitudinal velocity profile (us) of laboratory study and empirical equations in centerline for erodible bed and fixed bed shown by Mozaffari modified equation with Standar Error (SE) are 0.08 and 0.09 respectively. The smallest difference between longitudinal velocity profile of field study and empirical equations in centerline shown by Johannesson and Parker equation with Standar Error (SE) is 0.01. Transversal velocity profiles (vs) in sharp open channel bend have two characteristics, in centerline it reaches maximum magnitude near the bed (0.05h< z < 0.01h) and when closer to the bed (< 0.01h) velocity profiles is minimum. The smallest difference between transversal velocity profile (vs) of flume study and empirical equations in centerline for erodible bed and fixed bed shown by Seo & Jung modified equation with Absolute Error (AE) are 0.02 and 0.03 respectively. Transversal velocity profile obtained from Seo & Jung modified equation is good enough, the trend of velocity profile is decreasing when the location is closer to water surface. Flow vorticity for erodible bed generated maximum magnitude in centerline where R= 130 cm and angle of 60o, the magnitude is -17.85. This condition corresponds to maximum scouring which is measured by point gauge whereas minimum vorticity occurred in inner bank where R= 110 cm and angle of 180o, the magnitude is -0.01 which agree to the measuring result. Keyword: longitudinal velocity profile, transversal velocity profile, vorticity